Antiaging, Stress Resistance, and Neuroprotective Efficacies of Cleistocalyx nervosum var. paniala Fruit Extracts Using Caenorhabditis elegans Model. (29th November 2019) - Prasanth, Mani Iyer; Brimson, James Michael; Chuchawankul, Siriporn; Sukprasansap, Monruedee; Tencomnao, Tewin
Abstract : Plant parts and their bioactive compounds are widely used by mankind for their health benefits. Cleistocalyx nervosum var. paniala is one berry fruit, native to Thailand, known to exhibit various health benefits in vitro . The present study was focused on analyzing the antiaging, stress resistance, and neuroprotective effects of C. nervosum in model system Caenorhabditis elegans using physiological assays, fluorescent imaging, and qPCR analysis. The results suggest that the fruit extract was able to significantly extend the median and maximum lifespan of the nematode. It could also extend the healthspan by reducing the accumulation of the "age pigment" lipofuscin, inside the nematode along with regulating the expression of col-19, egl-8, egl-30, dgk-1, and goa-1 genes. Further, the extracts upregulated the expression of daf-16 while downregulating the expression of daf-2 and age-1 in wild-type nematodes. Interestingly, it could extend the lifespan in DAF-16 mutants suggesting that the extension of lifespan and healthspan was dependent and independent of DAF-16-mediated pathway. The fruit extract was also observed to reduce the level of Reactive Oxygen Species (ROS) inside the nematode during oxidative stress. The qPCR analysis suggests the involvement of skn-1 and sir-2.1 in initiating stress resistance by activating the antioxidant mechanism. Additionally, the fruit could also elicit neuroprotection as it could extend the median and maximum lifespan of transgenic strain integrated with A β . SKN-1 could play a pivotal role in establishing the antiaging, stress resistance, and neuroprotective effect of C. nervosum. Overall, C. nervosum can be used as a nutraceutical in the food industry which could offer potential health benefits.